Expression Of PhaC1 And PhaC2 From Pseudomonas Sp. USM4-55 In Escherichia Coli Expression System - Ghani, Balqis Ab. (2007)
Polyhydroxyalkanoates (PHAs) are synthesized intracelullarly by a variety of microorganisms as reserve materials for carbon and energy source. PHA synthase (PhaC) is the key enzyme in the polymerization of PHAs. Pseudomonas sp. USM4-55 is a local isolate which is able to produce a blend of short chain length and medium chain length of polymer. Genes coding for PhaC (phaC1 and phaC2) from Pseudomonas sp. USM4-55 were amplified (each with a size of 1.7 kb) from the genomic DNA, cloned into pGEMR-T for sequencing and then expressed. For expression studies, pQE-30 was used as the expression vector under the control of PT5 promoter. These clones were named pQE-C1 and pQE-C2, and were induced with 0.01 mM of isopropyl-p-Dthiogalactoside (IPTG) at ODeoo of 0.6.